PENGARUH BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN KELAS IIB CILACAP - Anjani, Regalia Mala; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of workload on employee job satisfaction at Class IIB Correctional Institution Cilacap. This research uses quantitative and non-probability techniques by applying a saturated sampling of 61 people. The data collection technique was carried out using the distribution of questionnaires to respondents through Google Forms. There are 24 statement items that are used as indicators in the study. The data analysis technique used is through the normality test, simple linear regression test, significance test, and determination test processed using IBM SPSS software version 27. The results showed that there is an influence of workload on job satisfaction. The results of the determination test were obtained with an R Square value of 0.114 which indicates that the workload variable has an influence of 11.4% on the work satisfaction variable, while other variables influence the remaining 88.6%. Keywords: Workload; Job Satisfaction; Correctional Officers